A Descriptive Investigation of Infant Feeding Bottles Marketed in the UK Designed to Replicate Breastfeeding and the Evidence That Underpins Them - Clare Maxwell; Becky Self; Kathryn Bould (Maternal and Child Nutrition, 2025)
ABSTRACT Scant attention has been given to the marketing of infant feeding bottles and teats with claimed equivalence to breastfeeding. Such bottles are purported as having ‘breast‐like’ qualities and to be interchangeable with breastfeeding, encouraging breastfeeding mothers to combine breast and bottle feeding. However, the introduction of bottle feeding alongside breastfeeding can have a negative impact on breastfeeding duration and lead to cessation. We investigated features of infant feeding bottles marketed in the United Kingdom to replicate breastfeeding and appraised the underpinning evidence. We searched online to identify the most popular bottles marketed for breastfeeding in the United Kingdom and captured marketing materials from the bottle brand websites, importing them into NVivo11 for data analysis. We coded data in relation to features of bottles associated with breastfeeding and used Johanna Briggs Institute (JBI) critical appraisal tools to appraise the evidence used to underpin the bottle features. We identified 10 bottle brands and 8 main advertised features of bottles aligned to breastfeeding. Features included bottles that simulated the breast, imitated breastfeeding physiology and aided combined breast and bottle feeding. Scientific evidence to support the bottle features was scarce, misleading, and inadequate, with only one study deemed to be high quality. Our findings show that infant feeding bottles are being marketed as equivalent to breastfeeding; however, the scientific evidence used to support features of these bottles is almost non‐existent. Research on the impact of the marketing of bottles on breastfeeding and more effective controls of bottle company advertising are needed.